A importância das interações nas práticas pedagógicas de 4ª para 5ª série do ensino fundamental de oito anos - Santos, Ondina Maria Alves de Almeida dos (2007)
Based on Vygotsky theoric s postulations, this work has the purpose og discussing and analysing the interactions observed in pedagogical practices in class-room, experienced by a group of teachers and students of a class passing from the 4th to the 5th serie of the eight years s fundamental education in a private net located at the Western Zone of the Rio de Janeiro city. For this purpose, a qualitative research has been adopted, having as instrument the observation s register done in the class-room of the elected group and questionnaires have been applied to the subjects that search: teachers and students of the 4th and 5th series. The data s analyse made according with the Content Analyse allowed three three categories to be stablished: passage from the 4th to the 5th serie; teacher-student interactions; student-student interactions. Based on that it is wished to identify the form by which these interaction s modalities affects the teaching-apprendiceship process, once difficulties are always related to that passage. Difference of conducts have been observed in the interaction of teacher-student from one year to another, so as differences in the pedagogical practices adopted by teachers according each considered serie. It has been noted that the different modalities of interaction occurred during this passage are not favourable to the developpment of the student s autonomy viewing the new demands and situations of teaching/apprenticeship which occurs in the 5th serie.